Papillary Adenocarcinoma - Tae-Se Kim; Byung-Hoon Min (Yong Chan Lee, 2021)
Gastric papillary adenocarcinoma is one of the histological variants of gastric cancer that shows more aggressive clinicopathological behavior compared to tubular adenocarcinoma. Previous studies have reported higher lymphovascular and submucosal invasion rates for papillary adenocarcionoma than those of tubular adenocarcinoma. However, the current guidelines categorize papillary adenocarcinoma and tubular adenocarcinoma together as differentiated-type tumor and have recommended the same endoscopic submucosal dissection criteria. Thus, concerns have been raised regarding the appropriateness of the current policy. To validate the current guidelines, the lymph node metastasis rate from surgical specimen studies as well as the long-term outcomes of endoscopic submucosal dissection for papillary adenocarcinomas need to be taken into consideration. In this review, I aimed to review the current understanding of the clinical and pathological features of papillary adenocarcinoma. In addition, I aimed to generate an integrated view regarding the outcomes of endoscopic submucosal dissection and surgery for papillary adenocarcinoma in order to evaluate the appropriateness of the current guidelines.